Synthesis and Evaluation of Herbal Chitosan from Ganoderma Lucidum Spore Powder for Biomedical Applications - Li-Fang Zhu (Nature Portfolio, 2018)
Abstract Chitosan is an extremely valuable biopolymer and is usually obtained as a byproduct from the shells of crustaceans. In the current work, chitosan is obtained from an herbal source (Ganoderma lucidum spore powder (GLSP)) for the first time. To show this, both standard (thermochemical deacetylation, (TCD)) and emerging (ultrasound-assisted deacetylation (USAD)) methods of chitosan preparation were used. The obtained chitosan was characterized by elemental analysis, XRD (X-ray diffraction), FT-IR (Fourier transform infrared spectroscopy) and thermogravimetric measurements. The process resulted in chitosan possessing comparable values of DD, [η] and $$\,\overline{{\rm{Mv}}}$$ Mv¯ to the commercial product. Chitosan obtained via both processes (TCD and USAD) displayed excellent biocompatibility; although the USAD prepared biopolymer exhibited significantly improved fibroblast (L929 cell) viability and enhanced antibacterial zones for both Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus). The findings of new herbal chitosan mark key developments of natural biomaterials; marking a potential shift from conventional sea-based organisms.